FENETRE study: quality-assured follow-up of quiescent neovascular age-related macular degeneration by non-medical practitioners: study protocol and statistical analysis plan for a randomised controlled trial. Issue 5 (11th May 2021) - Learoyd, Annastazia E; Tufail, Adnan; Bunce, Catey; Keane, Pearse A; Kernohan, Ashleigh; Robinson, Emily; Jaber, Alijazy; Sadiq, Saqlain; Harper, Robert; Lawrenson, John; Vale, Luke; Waterman, Heather; et al.
Abstract : Objective: Management of age-related macular degeneration (AMD) places a high demand on already constrained hospital-based eye services. This study aims to assess the safety and quality of follow-up within the community led by suitably trained non-medical practitioners for the management of quiescent neovascular AMD (QnAMD). Methods/design: This is a prospective, multisite, randomised clinical trial. 742 participants with QnAMD will be recruited and randomised to either continue hospital-based secondary care or to receive follow-up within a community setting. Participants in both groups will be monitored for disease reactivation over the course of 12 months and referred for treatment as necessary. Outcomes measures will assess the non-inferiority of primary care follow-up accounting for accuracy of the identification of disease reactivation, patient loss to follow-up and accrued costs and the budget impact to the National Health Service. Ethics and dissemination: Research ethics approval was obtained from the London Bloomsbury Ethics Committee. The results of this study will be disseminated through academic peer-reviewed publications, conferences and collaborations with eye charities to insure the findings reach the appropriate patient populations. Trial registration number: NCT03893474 .